Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1016/s1010-7940(01)00572-3
|View full text |Cite
|
Sign up to set email alerts
|

Off-pump coronary artery bypass surgery for critical left main stem disease: safety, efficacy and outcome

Abstract: OPCAB surgery is safe and effective in patients with critical LMS disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
2
8

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 20 publications
6
49
2
8
Order By: Relevance
“…A standardized OPCAB approach in high-risk patients does not come at a price of less complete revascularization. This is an important aspect that has been highlighted to be a crucial predictor for the long-term outcome [7,8], but has also been reported to be a major argument against OPCAB [11,24,25]. Our findings are supported by Puskas et al [8] who demonstrated feasibility of complete revascularization using OPCAB.…”
Section: Discussionsupporting
confidence: 81%
“…A standardized OPCAB approach in high-risk patients does not come at a price of less complete revascularization. This is an important aspect that has been highlighted to be a crucial predictor for the long-term outcome [7,8], but has also been reported to be a major argument against OPCAB [11,24,25]. Our findings are supported by Puskas et al [8] who demonstrated feasibility of complete revascularization using OPCAB.…”
Section: Discussionsupporting
confidence: 81%
“…Numerous studies have shown favourable outcomes with OFP surgery in patients with LMS disease (7)(8)(9). Certainly, the uses of stabilizers to steady the heart and intracoronary shunts to permit continued myocardial perfusion during performance of the distal anastomoses have contributed to this.…”
Section: Discussionmentioning
confidence: 99%
“…The studies included in this review have shown better or at least the same outcomes for OFP surgery of patients with LMS disease (8)(9)(10). However, the ROOBY trial involving 2,203 male patients has demonstrated in the whole population (LMS and non-LMS disease) that at 1-year follow-up patients undergoing a beating heart operation experienced worse composite outcomes i.e., mortality, repeat revascularization, or myocardial infarction than did patients in the ONP (28).…”
Section: Controversiesmentioning
confidence: 91%
See 2 more Smart Citations